Seed germination characteristics in different storage time of Gmelina arborea treated with ultrafine bubbles priming - ISKANDAR Z. SIREGAR; KARIMA FAUZIAH MUHARAM; Y. ARIS PURWANTO; DEDE J. SUDRAJAT (Society for Indonesian Biodiversity, 2020)
Abstract. Siregar IZ, Muharam KF, Purwanto YA, Sudrajat DJ. 2020. Seed germination characteristics in different storage time of Gmelina arborea treated with ultrafine bubbles priming. Biodiversitas 21: 4558-4564.  Gmelina (Gmelina arborea) seed collected from tropical Indonesian forest experience seed deterioration during storage which is relatively faster than the gmelina seeds originating from temperate regions, such as India and Myanmar. Various treatments have been made to improve the seed viability and vigor after storage through various invigoration techniques. However, the utilization of promising novel technology such as ultrafine bubbles (UFB) has not been evaluated yet. The objective of this study was to determine the effect of seed priming using UFB, polyethylene glycol (PEG), and gibberellic acid (GA3) on the viability and vigor of gmelina seeds that have been stored for one and two years. This study was conducted by employing Completely Randomized Design (CRD) using three replicates. The study showed priming treatment had significant effect and formed average germination capacity of 80% for the seed stored for 1 year.  On the other hand, the priming treatment using PEG-0.8 MPa was the best treatment for germination capacity of 74.67% on 2 years stored seeds. UFB had significant effect on germination capacity, germination rate, growth uniformity, and germination value. This result was expected due to reactive oxygen species (ROS) produced by micro-nano bubbles that could increase physiological activity of the seed cells.